2007
DOI: 10.1177/000313480707300409
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of Trauma in the Elderly

Abstract: To review the trends of trauma in the elderly experienced at our trauma center compared with other Level I trauma centers. This was a retrospective trauma registry analysis (1996–2003) of 2783 blunt trauma in elderly (BTE) and 4568 adult (BTA) patients in a Level 1 trauma center. Falls and motor vehicular crashes were the most common mechanisms noted in 47 per cent and 31 per cent (84% and 13% in BTE, 25% and 42% in BTA). BTE were sicker, with higher Injury Severity Scores (ISS), lengths of stay, and mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 27 publications
1
7
1
2
Order By: Relevance
“…A recent study found that elderly patients with blunt trauma suffered a higher mortality at any ISS. [ 20 ] A study by Tornetta et al . addressed factors affecting morbidity and mortality in elderly trauma patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that elderly patients with blunt trauma suffered a higher mortality at any ISS. [ 20 ] A study by Tornetta et al . addressed factors affecting morbidity and mortality in elderly trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients have a higher mortality for various reasons, including an increase in late mortality (>24 hours) due to in-hospital complications and a higher incidence of preexisting medical conditions, of which cardiac disease, diabetes mellitus, coagulopathy, neurologic disease, chronic obstructive pulmonary disease, malignancy, chronic kidney disease and liver disease were most commonly observed. [ 7 20 23 – 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that older women are substantially less able than young women to absorb energy in their upper extremities during a push-up task that simulates arresting a fall. This may contribute to the increase with age in the prevalence of fall-related hip fracture (10,11) and head and neck injury (12)(13)(14)(15). To place these results in the context of the ability to safely arrest a fall, it is useful to compare our observed energy absorptions with measures of the average energy content of a forward fall (16).…”
Section: Discussionmentioning
confidence: 99%
“…5,9,11,16 Falls historically accounted for 10 to 17 per cent of RF. Presently, falls are emerging as the most common etiology of trauma 23 due to a rapidly growing elderly population with fragile, osteopenic bones. Falls were the leading cause of trauma noted in 43 per cent of blunt injuries and 28 per cent of RF in this study.…”
Section: Discussionmentioning
confidence: 99%